Information and Communication Technology (ICT) and its Practice in Educational Evaluation - Hernández, Ronald M. (2019)
The ways in which pedagogical practices have evolved and how to understand the teaching and learning process are different. With the use of the Internet, the sources of information and evaluation are amplified, and educational agents within virtual education play an important role, reflecting on a new paradigm of learning and knowledge construction. From the theoretical review carried out in this document, aspects for virtual education and the tendency to an evaluative practice that does not deal exclusively with the classroom are exposed, since the intercommunication tools become and contribute to a new pedagogical practice focused on learning, giving rise to a more active role for students.